Analysis of a few verbs (based on the 16–17th century texts of the Grand Duchy of Lithuania) - Smetonienė, Anželika (Lietuvių kalba, 2014)
This article analyses a few borrowed verbs found in the ancient Lithuanian writings of the 16–17th century Grand Duchy of Lithuania. They are: bū̃bnyti, -ija, -ijo ‘to beat a drum, to beat or knock with something; fig. to speak widely', sū̃dyti, -ija, -ijo ‘to investigate a case in court, to judge; to condemn; to solve, consider; to advise', triū̃byti, -ija, -ijo ‘ to blow a trumpet, to tootle; to cry, to shout loudly; to gulp, to guzzle, to slurp. Their cognates bū̃bnas ‘a drum; fig. a bleak place with no grass, a shore, a bank; the colour of (playing) cards, sū̃das ‘a public, state body to consider court cases, a court; court premises; court proceedings; court decision, verdict, punishment; judge; expression of opinion, assessment, triūbà ‘a wooden or metal pipe-shaped wind instrument, a pipe (musical instrument), a horn, trumpet; a pipe; a curb; a chimney pipe; binoculars'. Some Lithuanian suffixes (e.g., -avo-) are more common only in verbs of a foreign origin, whereas -y-/-i- are equally frequent in the composition of Lithuanian derivatives formed from non-borrowed nouns. On the basis of the principles of word formation in Lithuanian and by means a comparison with the Slavic language data, the present article is an attempt to show how such verbs formed from borrowed root segments and the suffixes -y-/-i- can be interpreted. The Slavic language data were obtained from the etymological and historical dictionaries of Old Belarussian, Old Ukrainian, Old Polish, Old Russian and the dictionaries of Belorussian, Ukrainian, Polish, Russian dialects and the Slavic proto-language.
Keywords: none